PENINGKATAN HASIL BELAJAR MURID PADA MATA PELAJARAN PKN MELALUI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW DI KELAS V - Asmin, Ma’rifaul (Global Journal Teaching Professional, 2023)
This research aims to determine the increase in learning outcomes and student activities in the Civics learning process through the jigsaw type cooperative learning model in class V of SDN 302 Lattae Kec.Kindang, Bulukumba Regency. This type of research is classroom action research. Classroom Action Research (PTK) aims to improve various real and practical problems in improving the quality of classroom learning which are experienced directly in interactions between teachers and students who are learning. The subjects of this research were class V students at SD 302 LATTAE, in the odd semester of the 2022/2023 academic year with a total of 20 students, with heterogeneous student conditions. The implementation in the Civics learning process is through a jigsaw type cooperative learning model, namely students are observed from the start of learning, core activities (grouping process), and evaluation. Civics learning outcomes in cycle II showed an improvement and all students had complete learning outcomes. Based on the increase in the value of learning outcomes in cycle II mentioned above, it can be interpreted that the revision of actions taken in cycle II in the learning process using a jigsaw type model has proven to be effective. Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar dan aktivitas murid dalam proses pembelajaran PKn melalui model pembelajaran kooperatif tipe jigsaw di kelas V SDN 302 Lattae Kec.Kindang, Kab.Bulukumba. Jenis penelitian ini adalah penelitian tindakan kelas (classroom action research). Penelitian Tindakan Kelas (PTK) bertujuan untuk memperbaiki berbagai persoalan nyata dan praktis dalam peningkatan mutu pembelajaran dikelas yang dialami langasung dalam interaksi antara guru dengan siswa yang sedang belajar. Subjek penelitian ini adalah murid kelas V SD 302 LATTAE, pada semester ganjil tahun pelajaran 2022/2023 dengan jumlah murid sebanyak 20 orang, dengan keadaan murid yang heterogen. Adapun pelaksanaannya dalam proses pembelajaran PKn melalui model pembelajaran kooperatif tipe jigsaw yaitu murid diamati sejak awal pembelajaran, kegiatan inti (proses pengelompokan), dan evaluasi. hasil belajar PKn pada siklus II menunjukkan adanya peningkatan dan semua siswa memiliki hasil belajar yang tuntas. Berdasarkan peningkatan nilai hasil belajar pada siklus II tersebut di atas, maka dapat diinterpretasikan bahwa revisi tindakan yang diambil pada siklus II dalam proses pembelajaran dengan model tipe jigsaw terbukti efektif.